2019
DOI: 10.1002/mc.23015
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide expression profiling‐based copy number variations and colorectal cancer risk in Chinese

Abstract: Genetic factors play important roles in colorectal carcinogenesis. This study was aimed to evaluate the effects of gene expression‐related copy number variations (CNVs) on the risk of colorectal cancer in Chinese. Expression Quantitative Trait Locus (eQTL) mapping was conducted to explore the most regulatable gene expressions by CNVs among the whole genome based on publicly available data. Then a case‐control study was performed to evaluate the associations between copy numbers of the most regulatable genes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Researchers found that the prognosis of patients with the same cancer type can be quite different, and even patients of the same pathological type have signi cant differences in prognosis [5][6][7]. Through NGS sequencing and related research on a large number of tumor tissue samples from colon cancer patients, We found that the prognosis is related to patients' TMB, MSI, CNV and other genomic characteristics [8][9][10][11][12][13][14][15]. Taieb et al[8] investigated the mutations frequence and prognostic value of BRAF and KRAS in MSI and MSS Stage III Colon Cancer.They con rmed signi cant differences in mutation frequency of BRAF and KRAS and prognosis of patients in MSI-H and MSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers found that the prognosis of patients with the same cancer type can be quite different, and even patients of the same pathological type have signi cant differences in prognosis [5][6][7]. Through NGS sequencing and related research on a large number of tumor tissue samples from colon cancer patients, We found that the prognosis is related to patients' TMB, MSI, CNV and other genomic characteristics [8][9][10][11][12][13][14][15]. Taieb et al[8] investigated the mutations frequence and prognostic value of BRAF and KRAS in MSI and MSS Stage III Colon Cancer.They con rmed signi cant differences in mutation frequency of BRAF and KRAS and prognosis of patients in MSI-H and MSS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also found that TMB was associated with the treatment outcomes in patients with colorectal cancer [13][14]. Wang et al [15] studied the genome-wide expression pro ling-based copy number variations and colorectal cancer risk in Chinese.Their study suggested that the ampli ed copy number of HLA-DQB1 is associated with lower risk of colorectal cancer and able to induce the apoptosis of colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…This sequencing technology objectively reflects gene expression and accurately distinguishes cells at different developmental stages, thereby revealing cell types, subtypes, states and developmental trajectories. By combining cell-specific DNA barcodes with specific mRNA molecular markers during reverse transcription for many sequencing technologies, the aim is to improve the sequencing accuracy and obtain high-throughput sequencing data [ 40 ]. In addition, single-cell optical phenotyping and expression sequencing (SCOPE-Seq) is a scalable technique that combines live-cell imaging with scRNA-seq to obtain images, movies or other phenotypic data from single cells by microscopy and links this information directly to genome-wide expression profiles [ 58 ].…”
Section: Single-cell Sequencing Technologymentioning
confidence: 99%